Cortical microarchitecture and remodeling-associated gene expression related to oral cancer prognosis - Daniella Guedes de Figueiredo LOPES; Érica Fernanda PATRICIO; Neuza Maria Souza Picorelli ASSIS; Cláudia Malheiros COUTINHO-CAMILLO; Fabio de Abreu ALVES; Luiz Paulo KOWALSKI; Katharina JÄHN-RICKERT; Björn BUSSE; Gustavo Davi RABELO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The objective of this study was to assess the remodeling-associated gene expression in the mandible of patients diagnosed with oral squamous cell carcinoma (OSCC), investigating the cortical microarchitecture, and their influence on disease-free survival (DFS) and overall survival (OS) rates. A total of twenty-four patients who underwent mandibulectomy for OSCC treatment had two bone fragments harvested from the mandible for gene expression (RANK, RANKL, OPG, and SOST), and microarchitecture analysis, including bone volume, surface, mineral density, degree of anisotropy, and fractal dimension. The prognosis of the patients was assessed. The results revealed that RANK, RANKL, and SOST were predominantly downregulated, while OPG was completely downregulated. Tumors located adjacent to the posterior region of the mandible (p = 0.02), with a bone mineral density below 1.03 g/cm3 HA (p = 0.001), and a bone volume less than 86.47% (p = 0.03) were associated with poor outcomes. In conclusion, bone-remodeling-associated genes exhibited downregulation in the cortex of the mandible in OSCC patients. Additionally, the tumor's location within the mandible, bone volume, and cortical bone mineral density were identified as factors impacting DFS.